Unlocking the Future of Village Governance: Legal Counseling and Digital Transformation - Yarni, Meri; Irwandi, Irwandi; Kosariza, Kosariza; Netty, Netty; Bafadhal, Faizah (Jurnal Karya Abdi Masyarakat, 2023)
This Community Service Program was carried out in Danau Kedap Village, Maro Sebo Subdistrict, Muaro Jambi Regency, focusing on the importance of digitalization in village governance. Village governance involves the collaboration of the village area, its community, and the local government. This program aimed to increase the village government's understanding of how digitalization can improve administrative efficiency, transparency, and accountability. The goal was to provide legal counseling to enhance the knowledge of village officials on the role of digitalization in governance, and to explore solutions to challenges in daily governance tasks. The methods included lectures, discussions, and question-and-answer sessions to encourage active participation. The expected outcome is to improve the village government's administrative competence and service delivery. This initiative aims to promote the adoption of digital tools in governance processes, ultimately making village administration more efficient, transparent, and modern. The contributions of this project are significant in enhancing governance practices in the village, providing a model for other regions to follow.